Governança corporativa: a importância das auditorias internas na estrutura de governança de empresas - Libeck, Paulo Rodolfo Mota (Brasil, 2024)
This article explores the interdependence between internal auditing and corporate governance, highlighting the mutual benefits of this relationship for the effectiveness of organizational operations. The research adopts a descriptive and qualitative approach, using a comparative method between three case studies of companies from different regions of the world: Indonesia, Saudi Arabia and Greece. The analysis seeks to identify how these organizations implemented effective internal audits, highlighting the benefits that this practice brought to corporate governance. Content analysis was the technique chosen to treat the data, aiming to identify the differences and similarities between the cases and understand how corporate governance benefits from this interdependence with internal auditing. In the three cases analyzed, it was possible to observe that companies with well-structured internal audits were able to increase stakeholder confidence, promote regulatory compliance and strengthen their market position. The research concludes that internal auditing should not be seen only as a control mechanism, but as a fundamental strategic tool for strengthening corporate governance and creating a more ethical and efficient organizational environment.